Neither imperial nor national? The archival trails and legacies of (post)Ottoman-Armenians - Ketsemanian, Varak; Der Matossian, Bedross (Archival science, 2025)
Unlike Greeks, Arabs and Bulgarians, whose trajectories from imperial subjecthood to national states have been studied in much detail, the post-Ottoman legacies of the Armenians defy the accepted categories of "imperial" and “national.” Having neither an independent state (excluding the brief interlude of the First Republic 1918–1920) until 1991 nor a fully accepted citizenship status in the Turkish Republic, the dispersion of the surviving Ottoman-Armenians and their archives reflects this liminality that characterized their experiences throughout the twentieth century as they crisscrossed various legal categories. Serving as a guide to some of the intellectual and methodological pitfalls that underlie the study of imperial subjects in an age where national citizenship is the dominant political unit worldwide, this article highlights some of the major archival repositories that house collections of Ottoman-Armenian documents but also discusses some of the challenges associated with using or relying on them. We argue that a sound approach to a shared late Ottoman history is to critically assess the existing Armenian materials by taking them out of the—epistemological—shadow of the Armenian Genocide. Acknowledging the many difficulties that linger and hamper a more efficient and analytically engaging usage of the enormous mass of the material that Ottoman Armenians left behind, we, nonetheless, believe that they are immensely valuable and vital for a more complex, sophisticated and analytically viable reconstruction of late Ottoman lives. It is only through a consistent engagement with the various ways in which scholars have been studying the late history of Ottoman-Armenians that we can begin to sketch answers to several fundamental questions, including “Do archives have an ‘ethnic’ identity in a (post)imperial context? If so, how ‘Armenian’ are the materials under study?,” “How does the physical dispersion of Ottoman-Armenian documents account for the historians’ archival choices and consequently for the shaping of the major contours of Armenian and Turkish historiographies throughout the twentieth century?.”